2013
DOI: 10.1111/1462-2920.12093
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus type IV pili mediate interactions with diatom‐derived chitin and point to an unexplored mechanism of environmental persistence

Abstract: Vibrio parahaemolyticus is a naturally occurring bacterium common in coastal waters where it concentrates in shellfish through filter feeding. The bacterium is a human pathogen and the leading cause of seafood-borne gastroenteritis. Presently there is little information regarding mechanisms of environmental persistence of V.parahaemolyticus or an accurate early warning system for outbreak prediction. Vibrios have been shown to adhere to several substrates in the environment, including chitin, one of the most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 53 publications
(97 reference statements)
4
47
0
Order By: Relevance
“…Type IV pilins, like the one detected in Synechococcus sp. WH7803, have also been reported to have a potential role in chitin adhesion in Vibrio (Frischkorn et al ., 2013). Hence, picocyanobacteria may appear to be more hostile microorganisms than previously anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Type IV pilins, like the one detected in Synechococcus sp. WH7803, have also been reported to have a potential role in chitin adhesion in Vibrio (Frischkorn et al ., 2013). Hence, picocyanobacteria may appear to be more hostile microorganisms than previously anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Other exudates may be involved in species-specific interactions. Chitin, produced as a component of the diatom frustule in some species (64), has been shown to stimulate expression of functional type IV pili in V. parahaemolyticus, resulting in an increase in adherence (64 (66). In another study, Kim et al (67) demonstrated that the raphidophyte Olisthodiscus luteus (later changed to Heterosigma akashiwo) inhibited the growth of V. alginolyticus by reactive oxygen species-mediated processes.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of chitin by vibrios involves multiple levels of gene regulation that govern motility, chemotaxis, extracellular polysaccharide and biofilm matrix protein synthesis and secretion, type IV pilus production, chitin-binding protein secretion, chitin surface attachment, biofilm formation, extracellular chitinase secretion, chitoporin expression, and competence (166,338,470,(520)(521)(522)(523). Association with insoluble materials may be the preferred lifestyle of vibrios, including deep-sea hydrothermal vent species (15,403,524), and regulatory systems involving TCSs, chemotaxis, QS, sRNAs, cAMP, c-di-GMP, alternative sigma factors, and the stringent response enable vibrios to optimize resource utilization and survival (Fig.…”
Section: An Example Of Microbial Interaction With Surfaces: Vibrio Chmentioning
confidence: 99%